Evaluating the Impact of Maternal Thyroxine Usage on Neonatal Thyroid Function and Procedural Burden - Dr.Najia al hojaili; Dr. Mohammad al Thobaiti; Dr. Ibrahim Kutbi; Dr. Helal Al Maliki; Dr. Attia al Zahrani; Zahraa Barwaji Alsalami; Nura Alansari; Dr. Samira AL Yamani; Dr. Liza Sallam; Attyat Algadi; Sadia Yamani (International Journal of Medical Toxicology and Legal Medicine, 2025)
Introduction: This present research study explores the impact of maternal thyroxine use on neonatal thyroid function and procedural burden. The research focuses on infants born to hypothyroid mothers prescribed thyroxine between January 2021 and December 2022. The objective is to assess the effects of maternal hormone usage on neonatal thyroid function and investigate the associated procedural burden. Methodology: A retrospective study was conducted, encompassing 2000 deliveries. The study group consisted of 400 infants born to hypothyroid mothers taking thyroxine, without hypertensive pregnancy disorders (HPP) or diabetes mellitus (DM) history. Dosage varied, with 250 mothers taking 75 micrograms/day and 150 mothers taking 50 micrograms/day. Neonatal thyroid function tests were performed on all infants to evaluate thyroid hormone levels. Procedural burden was assessed by analyzing the number of Caesarian sections due to failure to progress and the prevalence of respiratory distress syndrome (RDS) among admitted infants. Results: The sensitivity of the thyroid function test was 95% (95% CI: 90-98%). The specificity of the test was 98% (95% CI: 95-99%). The PPV of the test was 97% (95% CI: 93-99%). The NPV of the test was 99% (95% CI: 97-100%). The P value for the association between mode of delivery and RDS was 0.001.Thyroid function tests revealed normal results for all 400 infants despite maternal thyroxine usage. However, one infant displayed low TSH and significantly low thyroid function, despite the mother's normal thyroid function. RDS was prevalent among admitted infants, with a majority diagnosed. Among the total deliveries, 600 were normal births, while 300 involved Caesarian sections due to failure to progress. Conclusion: Maternal thyroxine usage in hypothyroidism mothers did not significantly impact neonatal thyroid function, as indicated by normal test results. However, the case of the single infant with low TSH and thyroid function necessitates further investigation. Additionally, the analysis revealed a procedural burden associated with hypothyroidism cases, with a notable number of Caesarian sections due to failure to progress and a prevalence of RDS among admitted infants.